Graphene-Based Sensors for Human Health Monitoring - Huang, Haizhou; Su, Shi; Wu, Nan; Wan, Hao; Wan, Shu; Bi, Hengchang; Sun, Litao (Frontiers in Chemistry, 2019)
Since the desire for real-time human health monitoring as well as seamless human-machine interaction increasing rapidly, plenty of research effort has been made to investigate wearable sensors and implantable devices in recent years. As a novel 2D material, graphene has aroused a boom in the field of sensor research around the world due to its advantages in mechanical, thermal, and electrical properties. There have been lots of graphene-based sensors for human health monitoring reported, including wearable sensors, as well as implantable devices, which can realize the real-time measurement of body temperature, heart rate, pulse oxygenation, respiration rate, blood pressure, blood glucose, electrocardiogram signal, electromyogram signal and electroencephalograph signal, etc. Herein, as a review of the latest graphene-based sensors for health monitoring, their novel structures, sensing mechanisms, technological innovations, components for sensor systems and potential challenges will be discussed and outlined.